1998
DOI: 10.4310/atmp.1998.v2.n4.a5
|View full text |Cite
|
Sign up to set email alerts
|

Classification of reflexive polyhedra in three dimensions

Abstract: We present the last missing details of our algorithm for the classification of reflexive polyhedra in arbitrary dimensions. We also present the results of an application of this algorithm to the case of three dimensional reflexive polyhedra. We get 4319 such polyhedra that give rise to K3 surfaces embedded in toric varieties. 16 of these contain all others as subpolyhedra. The 4319 polyhedra form a single connected web if we define two polyhedra to be connected if one of them contains the other.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
216
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 160 publications
(218 citation statements)
references
References 25 publications
(54 reference statements)
2
216
0
Order By: Relevance
“…It turns out, however, that we need far less than the above mentioned 201346 CWS for our classification scheme if we choose suitable refinements of our original definition of minimality. While there are several possibilities of doing this (see [22,24,27]), we will mention only the one that is most powerful for the case of four dimensions considered here. We call a polytope A C M^ r-maximal if A is reflexive w.r.t.…”
Section: Outline Of the Algorithmmentioning
confidence: 99%
See 3 more Smart Citations
“…It turns out, however, that we need far less than the above mentioned 201346 CWS for our classification scheme if we choose suitable refinements of our original definition of minimality. While there are several possibilities of doing this (see [22,24,27]), we will mention only the one that is most powerful for the case of four dimensions considered here. We call a polytope A C M^ r-maximal if A is reflexive w.r.t.…”
Section: Outline Of the Algorithmmentioning
confidence: 99%
“…we can interpret the first n entries of the j'th column of D • U as coordinates of Vj on Mfi n est-Similarly, the lines of W • D provide coordinates for the vertices of A* on Nfi nest , whereas U and W give the corresponding coordinates on the coarsest possible lattices. The intermediate lattices are in one-to-one correspondence to subgroups of the finite lattice quotient Mfi n est/M C oarsest and can be found by decomposing D into a product of triangular matrices as described in [24,27].…”
Section: Outline Of the Algorithmmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, Hibi [19] showed that the coefficients a i (P ) of a lattice polytope are symmetric, i.e., a i (P ) = a n−i (P ), if and only if P is reflexive. Kreuzer and Skarke [22,23] classified all reflexive polytopes in dimensions ≤ 4. For n = 2, 3, 4 there are respectively 16; 4, 319 and 473, 800, 776 reflexive polytopes (up to unimodular equivalence).…”
Section: Lattice Boxesmentioning
confidence: 99%